OFDM/CDMA channel quality estimation using K-means algorithm - Abrous, Mohammed; Yagoubi, Benabdellah; Cherifi, Abdelhamid (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This work aims to estimate the transmission channel quality and suggest a possible way to enhance the data rates to satisfy the increasing demand for higher data rates to a certain extent. The combination of any non-orthogonal subcarrier multiplexed (SCM) with CDMA needs a large bandwidth, hence a limited number of subcarriers and number of users as well as lower data rates. In contrast, orthogonal subcarriers such as the case of OFDM which are closely spaced due to their orthogonality property as well as to their reduced frequency selectivity fading are, therefore, crucial for increasing subcarriers and thus, increasing the data rates as well as the number of users. To describe the OFDM/CDMA technique in more detail, we performed a simulation using the software Scilab 5.5.2. In this simulation, we treat a simple example of a certain number of users using a bipolar orthogonal code, particularly, the Hadamard/Welsh code for the OCDMA, and the fast fourier transform (FFT) algorithm for the OFDM. For a more realistic simulation, we have introduced a gaussian white noise in the transmission channel and studied the effect of this noise on the eye diagram. Finally, to avoid the computational complexity in calculating the BER to study the OFDM/CDMA channel system quality, we have instead computed the bias and the variance of a noisy 16- quadrature amplitude modulation (QAM) constellation at the reception using the K-means algorithm.